2008
DOI: 10.1021/jf073309b
|View full text |Cite
|
Sign up to set email alerts
|

Cranberries and Cranberry Products: Powerful in Vitro, ex Vivo, and in Vivo Sources of Antioxidants

Abstract: Cranberry products and especially cranberry juice (CJ) have been consumed for health reasons primarily due to their effect on urinary tract infections. We investigated the quantity of both free and total (after hydrolysis) phenolic antioxidants in cranberry products using the Folin assay. The order of amount of total polyphenols in cranberry foods on a fresh weight basis was as follows: dried > frozen > sauce > jellied sauce. On a serving size basis for all cranberry products, the order was as follows: frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 42 publications
5
57
0
2
Order By: Relevance
“…Our results are in correspondence with Burdulis et al [24], where it was shown that the strongest antioxidant capacity possesses blueberry cultivar ''Berkeley'' (82.13 ± 0.51 %). Our results about the investigated berries like cranberries are in full correspondence with other reports that it is an excellent source of high-quality antioxidants and should be examined in human supplementation studies [33]. Bog bilberry water extracts contained polyphenol, anthocyanin-rich (pigment), and sugar/acid fractions by using ethyl acetate, acidic methanol (MeOH) and 0.01 N HCl.…”
Section: Discussionsupporting
confidence: 77%
“…Our results are in correspondence with Burdulis et al [24], where it was shown that the strongest antioxidant capacity possesses blueberry cultivar ''Berkeley'' (82.13 ± 0.51 %). Our results about the investigated berries like cranberries are in full correspondence with other reports that it is an excellent source of high-quality antioxidants and should be examined in human supplementation studies [33]. Bog bilberry water extracts contained polyphenol, anthocyanin-rich (pigment), and sugar/acid fractions by using ethyl acetate, acidic methanol (MeOH) and 0.01 N HCl.…”
Section: Discussionsupporting
confidence: 77%
“…However, our study shows that OA and UA can be readily taken in from raisins and dried cranberries as part of daily food consumption. As raisins and dried cranberries also contain various functional flavonoids (Zhao and Hall, 2007;Vinson et al, 2008), the combination of flavonoids and the triterpenes OA and UA provided by these fruits may be particularly beneficial for spot). Because we believed that these fruits contain only trace amounts of UA and OA, we did not analyze them by HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…This effect might be due to an elevation in apo A-I and a decrease in HDL particles clearance that is mediated by cranberry supplements, or in other words, by polyphenolic compounds (7,8,14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). On the other hand, quercetin, one of the most prominent flavonols of cranberry, can increase HDLassociated enzymes such as paraoxanase-1 (PON-1) (30).…”
Section: Discussionmentioning
confidence: 99%